Comparative morphology of extant raptorial Mantispoidea (Neuroptera: Mantispidae, Rhachiberothidae) suggests a non-monophyletic Mantispidae and a single origin of the raptorial condition within the superfamily - Ardila-Camacho, Adrian; Martins, Caleb Califre; Aspöck, Ulrike; Contreras-Ramos, Atilano (Zootaxa, 2021)
Adult external morphology of the extant raptorial Mantispoidea (Insecta: Neuroptera: Mantispidae and Rhachiberothidae) is compared emphasizing the morphology of the subfamily Symphrasinae as a key group to understand the phylogenetic relationships among the members of the superfamily. Plega dactylota Rehn, 1939 is thoroughly characterized in order to exemplify the morphology of the Symphrasinae. Additionally, following a review of the literature and examination of comparative material of Dilaridae, Berothidae, Rhachiberothidae and all Mantispidae subfamilies, a new interpretation of the components of the raptorial apparatus (i.e., head, prothorax, grasping forelegs, as well as integumentary specializations) is presented. Also, wing venation for these groups is reinterpreted, and new homology hypotheses for wing venation are proposed based on tracheation and comparative analyses. Given the high morphological divergence on the genital sclerites within the Mantispoidea, plus the confusing previous usage of neutral terminology and terms referring to appendages across taxonomic and morphological studies, we attempt to standardize, simplify, and situate terminology in an evolutionary context under the “gonocoxite concept” (multi-coxopod hypothesis). The remarkable morphological similarity of the genital sclerites of Symphrasinae and Rhachiberothidae (sensu U. Aspöck & Mansell 1994) with the Nallachinae (Dilaridae) was taken as a starting point to understand the morphology of other Mantispidae subfamilies. Based on these morphological comparisons, we provide a revised phylogenetic analysis of Mantispoidea. This new phylogenetic analysis supports a sister group relationship between the family Rhachiberothidae, comprising Rhachiberothinae and Symphrasinae, and the family Mantispidae, including the subfamily Mantispinae and its sister taxa Drepanicinae and Calomantispinae, which may represent a single subfamily. Based on these analyses, raptorial condition probably evolved a single time in these insects and subsequently became diversified in the two sister clades of the raptorial Mantispoidea.